Reassessment of American Joint Committee on Cancer Staging for Stage III Renal Cell Carcinoma With Nodal Involvement: Propensity Score Matched Analyses of a Large Population-Based Study - Han, Jianglong; Li, Qin; Li, Ping; Wang, Shijie; Zhang, Rui; Qiao, Yunfeng; Song, Qibin; Fu, Zhenming (Frontiers in Oncology, 2020)
Background: To assess the role of nodal involvement in stage III renal cell carcinoma (RCC) under the American Joint Committee on Cancer (AJCC) 8th staging system. We compare the survival outcomes of RCC patients with pT1-3N1M0 disease and those with pT3N0M0 or stage Ⅳ (stratified as pT4NanyM0 and pTanyNanyM1) disease in a large population-based cohort. Methods: A cohort of 3,112 eligible patients with RCC was identified from the Surveillance, Epidemiology, and End Results (SEER) database, registered from January 2004 to December 2015. Kaplan-Meier and Cox proportional hazards model were used to evaluate the overall survival (OS), and cancer-specific survival (CSS). The prognostic value of the modified stage for pT1-3N1M0 disease was assessed by the nomogram-based analyses. Propensity score matching (PSM) was used to adjust for potential baseline confounding. Results: Patients with pT1-3N1M0 disease showed similar survival outcomes (median OS 41.0 vs. 38.0 months, P = 0.77; CSS 45.0 vs. 39.0 months, P = 0.59) with pT4NanyM0 patients, whereas the significant better survival were found for pT3N0M0 patients. After PSM, comparable survivals were observed between pT1-3N1M0 group and pT4NanyM0 group, which were still significantly worse than the survival of pT3N0M0 patients. The modified stage ⅢA (pT3N0M0), ⅢB (pT1-3N1M0, pT4NanyM0), and Ⅳ (pTanyNanyM1) showed higher predictive accuracy than AJCC stage system in the nomogram-based analyses (concordance index: 0.70 vs. 0.68, P < 0.001 for OS; 0.71 vs. 0.69, P < 0.001 for CSS). Conclusions: The pT1-3N1M0 RCC might be reclassified as stage IIIB together with pT4NanyM0 disease for the better prediction of prognosis, further examination and validation are warranted.